Benchmarking as a tool for assessing the quality of research management of students in agricultural universities of Ukraine - Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна (University of Agronomic Sciences and Veterinary Medicine of Bucharest, Romania. Ceres Publishing House., 2023)
The purpose of this article is to evaluate the quality of research management of students in agricultural universities of Ukraine using benchmarking. The external evaluation of agricultural higher education institutions (HEIs) of Ukraine was conducted on the basis of the data of the State Scientific Institution “Institute of education content modernization” and the Ministry of Education and Science of Ukraine regarding the results of the All-Ukrainian competition of student scientific papers in the fields of knowledge and specialties in 2019/2020 and 2020/2021 academic years. The leaders according to the results of participation in the II round of the competition in the analyzed period were 9 HEIs: Mykolaiv National Agrarian University (NAU), National University of Life and Environmental Sciences of Ukraine, Kharkiv Petro Vasylenko National Technical University of Agriculture, Lviv NAU, Sumy NAU, Vinnytsia NAU, Poltava State Agrarian Academy, Kharkiv NAU named after V. V. Dokuchayev, Polissia National University. They annually had more than 10 winners of the competition of various degrees. Other agricultural HEIs of Ukraine should focus on their indicators in order to improve the quality of research management of students. The obtained results enable agricultural universities not only to determine the leaders based on the number of works awarded with I, II or III degree diplomas in the All-Ukrainian competition, but also to evaluate, compared to them, their strengths and weaknesses; to get new ideas for research management of students; to plan further scientific activities taking into account the indicators of HEIs-leaders.

Метою цієї статті є оцінити якість керівництва науковою роботою здобувачів освіти в аграрних університетах України за допомогою бенчмаркінгу. Зовнішнє оцінювання аграрних закладів вищої освіти (ЗВО) України проведено на основі даних Державної наукової установи “Інститут модернізації змісту освіти” та Міністерства освіти і науки України щодо підсумків Всеукраїнського конкурсу студентських наукових робіт з галузей знань і спеціальностей у 2019/2020 і 2020/2021 навчальних роках. Лідерами за результатами участі в ІІ турі конкурсу в аналізованому періоді були 9 ЗВО: Миколаївський національний аграрний університет (НАУ), Національний університет біоресурсів і природокористування України, Харківський національний технічний університет сільського господарства імені Петра Василенка, Львівський НАУ, Сумський НАУ, Вінницький НАУ, Полтавська державна аграрна академія, Харківський НАУ імені В. В. Докучаєва, Поліський національний університет. Вони щорічно мали більше 10 переможців конкурсу різних ступенів. Інші аграрні ЗВО України повинні орієнтуватися на їх показники задля підвищення якості керівництва науковою роботою здобувачів освіти. Отримані результати дають можливість аграрним університетам не тільки визначити лідерів за показниками кількості робіт, нагороджених дипломами І, ІІ чи ІІІ ступеня у Всеукраїнському конкурсі, але й оцінити, порівняно з ними, свої власні сильні та слабкі сторони; почерпнути нові ідеї для керівництва науковою роботою студентів; спланувати подальшу наукову діяльність з урахуванням показників ЗВО-лідерів.
Бенчмаркінг як інструмент оцінювання якості керівництва науковою роботою здобувачів освіти в аграрних університетах України
Keywords: benchmarking; agricultural universities; Ukraine; management quality; student research papers; бенчмаркінг; аграрні університети; Україна; якість керівництва; студентські наукові роботи